“Soil” in ethnicity: Traditions of Russian ethnology tested by “perestroika” and postmodernism (problem statement) - Popkov, Yuri V. (The New Research of Tuva, 2023)
The author analyzes the ambiguity of the Russian discourse of ethnicity. It has become an overarching topic in anthropology and ethnography (ethnology). This ambiguity is stemming from transformations in the country’s social system and social and humanities knowledge, including ethnography/ethnology (ethnic studies). Therefore, in the article the consideration of the epistemological and ontological aspects of the topic of “soil”, as it is presented in ethnicity, is preceded by an analysis of the drastic changes of methodological objectives and challenges of the national study of peoples (ethnoses) in the post-Soviet period.The author comes to the conclusion that, by and large, there is no “soil” in ethnicity. The latter is understood within the framework of the constructivist methodological setting and reduced to ethnic identity. In fact, identity here has no ontological foundations and therefore no real ground.This issue is adequately reflected in Russian ethnology in its classical sense. According to A. V. Golovnev, initially it is a “soil” science, it means that it is based on the study of “real circumstances and needs” of peoples. A solution of this problem in relation to our time is possible with the use of modern research methods. It is necessary to take into account not only options of an external view on ethnic culture (outside), but also characteristics of its internal state (inside) in the culture bearers’ representations. In this context, interesting studies are conducted within the framework of Tuvinology. The author draws attention to them.The article suggests an idea about the need to develop the theory of ethnos taking into account the changed reality and applying modern research methods.
Keywords: ethnos; people; ethnicity; ethnic culture; ethnography; ethnology; ethnic studies; soil; Russia; Tuva; Tuvan culture; Tuvans